The evaluation of our newborns cases operated due to necrotizing enterocolitis - Korkmaz, Levent; Bastug, Osman; Daar, Ghaniya; Korkut, Sabriye; Halis, Hulya; Ozdemir, Ahmet; Ceylan, Mahir; Gunes, Tamer; Adnan Ozturk, Mehmet; Kurtoglu, Selim (Annals of Medical Research, 2021)
None